ChemInform Abstract: Sodium Azide as a Catalyst for the Hydration of Nitriles to Primary Amides in Water. Issue 39 (September 2015) - Bahrami, Kiumars; Khodaei, Mohammad Mehdi; Roostaei, Mohsen
Abstract Sodium azide is used for the first time as a mild and efficient catalyst for the conversion of a wide range of nitriles to the corresponding primary amides.